Comparison of Non-contact Tonometry and Goldmann Applanation Tonometry Measurements in Non-pathologic High Myopia - Wang, Peiyuan; Song, Yunhe; Lin, Fengbin; Wang, Zhenyu; Gao, Xinbo; Cheng, Weijing; Chen, Meiling; Peng, Yuying; Liu, Yuhong; Zhang, Xiulan; Chen, Shida (Frontiers in Medicine, 2022)
Purpose: To compare intraocular pressure (IOP) values obtained using Goldmann applanation tonometry (IOPGAT) and non-contact tonometry (IOPNCT) in a non-pathologic high myopia population. Methods: A total of 720 eyes from 720 Chinese adults with non-pathologic high myopia were enrolled in this cross-sectional study. Demographic and ocular characteristics, including axial length, refractive error, central corneal thickness (CCT), and corneal curvature (CC) were recorded. Each patient was successively treated with IOPNCT and IOPGAT. Univariate and multivariable linear regression analyses were conducted to detect factors associated with IOPNCT and IOPGAT, as well as the measurement difference between the two devices (IOPNCT-GAT). Results: In this non-pathologic high myopia population, the mean IOPNCT and IOPGAT values were 17.60 ± 2.76 mmHg and 13.85 ± 2.43 mmHg, respectively. The IOP measurements of the two devices were significantly correlated (r = 0.681, P < 0.001), however, IOPNCT overestimated IOPGAT with a mean difference of 3.75 mmHg (95% confidence interval: 3.60-3.91 mmHg). In multivariate regression, IOPNCT was significantly associated with body mass index (standardized β = 0.075, p = 0.033), systolic blood pressure (SBP) (standardized β = 0.170, p < 0.001), and CCT (standardized β = 0.526, p < 0.001). As for IOPGAT, only SBP (standardized β = 0.162, p < 0.001), CCT (standardized β = 0.259, p < 0.001), and CC (standardized β = 0.156, p < 0.001) were significantly correlated. The mean IOPNCT-GAT difference increased with younger age (standardized β = -0.409, p < 0.001), higher body mass index (standardized β = 0.091, p = 0.009), higher SBP (standardized β = 0.074, p = 0.027), thicker CCT (standardized β = 0.506, p < 0.001), and lower IOPGAT (standardized β = -0.409, p < 0.001). Conclusion: In the non-pathologic high myopia population, IOPNCT overestimated IOPGAT at 3.75 ± 2.10 mmHg. This study suggests that the difference between the values obtained by the two devices, and their respective influencing factors, should be considered in the clinical evaluation and management of highly myopic populations.